Effects of Mesh Size on Simulation Results of Water-Cooling Radiator for IGBT Module - 丁杰; 唐玉兔; 忻力; 胡昌发 (Kongzhi Yu Xinxi Jishu)
It comparatively analyzed CFD simulation results of IGBT water-cooled radiator with 0.5mm, 1mm and 2mm mesh size. Research results showed that the scheme of mesh size 0.5mm tended to be more accurate than the others on capturing the flow information and the computing results were the most accurate. A method of convection heat- transfer coefficient distribution mapping from fine mesh CFD model to coarse mesh finite element model were studied. The method is identical to fine mesh CFD model in the result of temperature and can be applied to air-cooling, oil-cooling radiator simulation analysis.